ChemInform Abstract: Prediction of Structural, Lattice Dynamical, and Mechanical Properties of CaB2. Issue 3 (22nd January 2013) - Vajeeston, P.; Ravindran, P.; Fjellvaag, H.
Abstract DFT calculations